2019
DOI: 10.1111/acel.13026
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term repopulation of aged bone marrow stem cells using young Sca‐1 cells promotes aged heart rejuvenation

Abstract: Reduced quantity and quality of stem cells in aged individuals hinders cardiac repair and regeneration after injury. We used young bone marrow (BM) stem cell antigen 1 (Sca‐1) cells to reconstitute aged BM and rejuvenate the aged heart, and examined the underlying molecular mechanisms. BM Sca‐1+ or Sca‐1− cells from young (2–3 months) or aged (18–19 months) GFP transgenic mice were transplanted into lethally irradiated aged mice to generate 4 groups of chimeras: young Sca‐1+, young Sca‐1−, old Sca‐1+, and old … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 25 publications
0
21
0
Order By: Relevance
“…Implantation of genetically-modified old human MSCs with tissue inhibitor of matrix metalloproteinase-3 or VEGF promotes angiogenesis, prevents adverse remodeling, and preserves cardiac function to a similar extent compared with young hMSCs[ 122 ]. Stem cell antigen 1 (Sca-1)+ MSCs resident in the heart increase angiogenesis, and activate cell proliferation in the infarcted heart, which improves cardiac function after MI[ 123 , 124 ]. Overexpression of neuron-derived neurotrophic factor rejuvenates human ADSCs and BM-MSCs from the elderly, reduces the ischemic area, and repairs cardiac function after MI by improving angiogenesis and decreasing apoptosis[ 125 , 126 ].…”
Section: Cellular Rejuvenation Strategiesmentioning
confidence: 99%
“…Implantation of genetically-modified old human MSCs with tissue inhibitor of matrix metalloproteinase-3 or VEGF promotes angiogenesis, prevents adverse remodeling, and preserves cardiac function to a similar extent compared with young hMSCs[ 122 ]. Stem cell antigen 1 (Sca-1)+ MSCs resident in the heart increase angiogenesis, and activate cell proliferation in the infarcted heart, which improves cardiac function after MI[ 123 , 124 ]. Overexpression of neuron-derived neurotrophic factor rejuvenates human ADSCs and BM-MSCs from the elderly, reduces the ischemic area, and repairs cardiac function after MI by improving angiogenesis and decreasing apoptosis[ 125 , 126 ].…”
Section: Cellular Rejuvenation Strategiesmentioning
confidence: 99%
“…By bone marrow reconstitution animal model, we also demonstrated that young bone marrow Scal-1 cells can rejuvenate age animal heart function after MI. Examination of the underlying molecular mechanisms revealed that young bone marrow Scal-1 cells secreted more growth factors, such as Tgfβ1 and Cxcl12, in order to regenerate the aged heart ( Li et al, 2018 , 2019 ). In this study, we also detected paracrine functional changes, with down-regulation of lnc-CYP7A1-1 in O hBM-MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…The potency of hBM-MSCs in the treatment of cardiovascular disease has been shown to decrease with the age of the donor ( Dong et al, 2018 ). This decreased potency of hBM-MSCs has a significant impact on the use of autologous stem cells for treating a predominantly older cohort of patients with cardiovascular disease ( Li S.-H. et al, 2013 ; Li et al, 2018 , 2019 ). Part of this reduced efficacy is due to hBM-MSCs taking on a senescent phenotype and losing their proliferative capacity ( Yan et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, studies in mice show the benefits of bone marrow replacement in models of aging or chronic disease. Heterochronic (young to old) bone marrow transplant in 20-22 month old mice improves angiogenesis via upregulation of Cxcl12, Vegf and the inflammatory response post-MI [172,174,208]. Young bone marrow cell transplantation can also improve cognitive function and muscle repair in aged mice, implying a greater scope for bone marrow cell aging on systemic tissue aging [209][210][211].…”
Section: Bone Marrow Transplant and Niche Remodelingmentioning
confidence: 99%